Peran Kecerdasan Emosional dalam Pengobatan Cystic fibrosis - Luthfiah Mawar; M. Agung Rahmadi; Helsa Nasution; Nurzahara Sihombing; Romaito Nasution; Milna Sari (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
This study investigates the role of emotional intelligence (EI) in cystic fibrosis (CF) treatment through a comprehensive meta-analysis of 47 studies involving 5,823 CF patients. Results affirm a significant positive correlation between EI and treatment adherence (r = 0.62, p < 0.001), as well as improved quality of life (QoL) for CF patients (β = 0.58, 95% CI [0.49, 0.67]). Regression analysis revealed that EI predicts 37% of the variance in lung function (FEV1) (R² = 0.37, F(1, 5821) = 3421.76, p < 0.001). Furthermore, patients with high EI scores exhibited significantly reduced levels of anxiety (d = -0.79) and depression (d = -0.83) compared to control groups. These findings extend previous research by Salovey et al. (2002) and Ceyhan et al. (2024) by identifying specific EI mechanisms influencing CF treatment outcomes. Unlike Cox et al.'s (2020) study focusing on the general population, our findings specifically demonstrate the effectiveness of EI-based interventions in improving clinical outcomes for CF patients, with an average FEV1 increase of 12% after 6 months of intervention. Lastly, mediation analysis indicated that emotion regulation (β = 0.31, p < 0.001), adaptive health behaviors (β = 0.28, p < 0.001), and utilization of social support (β = 0.22, p < 0.001) mediated the relationship between EI and CF treatment outcomes. These findings underscore the importance of integrating EI training into standard CF care protocols to enhance holistic treatment outcomes.